The influence of planning on the development of innovation in small and medium enterprises - Vujičić Slađana; Ravić Nenad; Nikolić Miloš (Trendovi u Poslovanju)
Innovations are one of the most important factors in the competitiveness of the enterprises in modern business conditions. Innovation is defined as the process of creating new (and differentiated) value for customers in the market, which can create a sustainable competition advantage. The goal of innovation is to create more successful future of the company, but this success does not happen by itself, but a purposeful implementation of the innovation process is required - which requires, in the first place, the planning of all phases and sub-processes.